Sulfonic acid group covalent organic framework core-shell material adsorbent, and preparation method and application thereof
Patent Information
- Application Number
- CN202611468401.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-27
AI Technical Summary
然而,现有COFs基吸附材料普遍存在以下不足:(1)作用机制单一:现有COFs吸附剂主要依赖单一的静电作用或π-π作用,缺乏多重作用机制的协同设计,难以实现复杂基质中结构相似生物碱的高选择性分离
本发明所得磺酸基共价有机框架核壳材料吸附剂可以对样品中异喹啉生物碱发挥良好吸附作用,表现出吸附容量高、吸附速率快、吸附选择性好、易循环使用等优点。本发明磺酸基共价有机框架核壳材料吸附剂的制备方法制备过程简单易行,操作方便,利于工业化生产;对样品中异喹啉生物碱的综合吸附性能优异,具有良好的应用前景。
Smart Images

Figure CN122974286A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of adsorption separation, and more particularly to sulfonic acid-based covalent organic framework core-shell material adsorbents, their preparation methods, and applications. Background Technology
[0002] Isoquinoline alkaloids are a large class of nitrogen-containing basic organic compounds widely distributed in natural plants, possessing a variety of significant pharmacological activities, including anti-inflammatory, antibacterial, antitumor, neuroprotective, and antidiabetic effects. For example, tetrandrine is used for antitumor and neuroprotective treatment, berberine for diabetes treatment, nuciferine for obesity prevention, bortine as an effective anticancer agent, and camptothecin for treating tumors, cardiovascular diseases, and cancer. Recently, four representative isoquinoline alkaloids were discovered in camphor tree seed kernels, including magnoflorine, tetrandrine, nancholine, and N-methylenenancholine. These alkaloids have important value in traditional Chinese medicine and modern drug development. For example, magnoflorine exhibits broad pharmacological activities, including antidiabetic, anti-inflammatory, and neuropsychiatric activities; nancholine shows potent acetylcholinesterase inhibitory activity associated with Alzheimer's disease. However, the coexistence of multiple structurally similar alkaloids at low concentrations in complex plant matrices presents a significant challenge to their isolation and purification. Therefore, there is an urgent need to develop reliable and effective methods for the isolation, purification, and quantification of these isoquinoline alkaloids from plant extracts.
[0003] Traditional solvent extraction techniques struggle to achieve efficient and selective separation of target components from structurally similar impurities, and generally suffer from inherent drawbacks such as long operation cycles, high processing times, large solvent consumption, and low resolution. While high-performance liquid chromatography (HPLC) improves separation accuracy to some extent, it remains limited by high equipment investment costs, small batch throughput, and difficulty in scaling up preparation, thus failing to meet the demands of industrial-scale preparation. Solid-phase extraction (SPE), or adsorption separation, is a widely used sample purification and enrichment technique based on the selective adsorption of target analytes on solid adsorbents. The adsorbent is the core of SPE technology, and its type and properties directly determine the method's recovery rate, selectivity, and sensitivity. Currently used commercial SPE adsorbents, such as octadecylsilane-bonded silica gel C18, cation exchange resins, macroporous adsorption resins, and silica gel, all have limitations when applied to alkaloid separation. For example, commercial stationary phases, such as C18, primarily rely on hydrophobic interactions, resulting in limited enrichment efficiency for polar analytes in aqueous matrices, and their poor selectivity often leads to co-extraction of interfering substances. While cation exchange resins can effectively capture protonated alkaloids, their gel-like frameworks are prone to swelling or shrinkage due to changes in solvent polarity, affecting stability and flow rate control, and shortening their lifespan. Macroporous adsorption resins mainly function through non-specific physical adsorption, making them susceptible to interference from impurities such as pigments and proteins, leading to insufficient selectivity and pore blockage. Furthermore, the strong interaction between the silanol groups on the silica gel surface and the basic nitrogen atoms of alkaloids often results in irreversible adsorption. Therefore, developing novel SPE adsorbents with high adsorption efficiency, good stability, and multiple interaction sites for the separation and purification of isoquinoline alkaloids remains a challenging yet highly significant task.
[0004] Covalent organic frameworks (COFs) are a class of crystalline porous materials composed of light elements (C, H, O, N, S) linked by strong covalent bonds. Their functional properties, such as high specific surface area, regular pore structure, and excellent chemical stability, make them promising for applications in the field of adsorption and separation. The pore size of COFs can be precisely adjusted by selecting building blocks of appropriate length; longer connecting layers usually result in larger pores. This design flexibility allows for the rational construction of COFs with specific pore sizes to suit target molecules. However, existing COF-based adsorbents generally have the following shortcomings: (1) Single action mechanism: Existing COF adsorbents mainly rely on single electrostatic interactions or π-π interactions, lacking synergistic design of multiple action mechanisms, making it difficult to achieve highly selective separation of structurally similar alkaloids in complex matrices. (2) Poor dispersibility and operability: Pure COF materials have low density and are prone to agglomeration, making them difficult to pack in solid-phase extraction columns, resulting in high back pressure, which is not conducive to practical applications. (3) Harsh synthesis conditions: The synthesis of most COFs requires high temperature, high pressure and long reaction time, which is not conducive to large-scale preparation and application. Therefore, developing a novel COFs-based solid-phase extraction adsorbent with precisely controllable pore size, multiple adsorption mechanisms, good dispersibility and mild preparation conditions is of great practical significance and application value for achieving efficient separation and enrichment of isoquinoline alkaloids.
[0005] Among the many key factors affecting adsorption performance, pore size plays a particularly important role. Pore sizes that are too small hinder the entry of large molecules, while pore sizes that are too large weaken the affinity between host and guest molecules, thus reducing adsorption capacity. Recent studies have shown that selective adsorption of compounds of different sizes and polarities can be achieved by controlling the pore size and surface chemistry of COFs. For example, Wang et al. systematically studied the adsorption performance of COFs with different pore sizes for perfluoroalkyl substances (PFAS), finding that the adsorption capacity was optimal when the COF pore size was 2.5–4.0 times the molecular size of the target analyte. This "pore size matching" principle provides important theoretical guidance for designing highly efficient adsorbents for specific molecules (Wang, W., Jia, Y., Zhou, S., & Deng, S. (2023). Removal of typical PFAS from water bycovalent organic frameworks with different pore sizes. Journal of Hazardous Materials, 460, 132522. https: / / doi.org / 10.1016 / j.jhazmat.2023.132522). Summary of the Invention
[0006] To address the aforementioned problems, this invention proposes a sulfonic acid-based covalent organic framework (COFs) core-shell adsorbent, its preparation method, and its application. This material uses mesoporous silica as the core and sulfonic acid-based COFs as the shell. The sulfonic acid groups are covalently fixed on the framework of the COFs shell. Through multiple synergies, including electrostatic interactions, π-π stacking effects provided by the aromatic framework of the COFs, hydrogen bonding effects provided by polar groups, and pore size matching effects, it achieves efficient and highly selective separation and enrichment of isoquinoline alkaloids.
[0007] To achieve the above objectives, the present invention is implemented according to the following technical solution: The first aspect of this invention provides a method for preparing a sulfonic acid-based covalent organic framework core-shell material adsorbent, comprising the following steps: S1. Preparation of aminated mesoporous silica (SiO2-NH2): Mesoporous SiO2 was dispersed in ethanol, 3-aminopropyltriethoxysilane (APTES) was added, the mixture was stirred and refluxed, and SiO2-NH2 was obtained after washing and drying. APTES is a silane coupling agent with a hydrolyzable ethoxy group (-OC2H5) at one end and an active amino group (-NH2) at the other. Anhydrous ethanol is used as the dispersion medium and co-solvent. APTES undergoes hydrolysis to generate silanol groups (Si-OH). The surface of SiO2 particles is rich in silanol groups (Si-OH). Under reflux heating, the Si-OH generated from the hydrolysis of APTES undergoes a siloxane condensation reaction with the Si-OH on the silica surface, forming Si-O-Si covalent bonds, thus fixing the aminopropyl group grafted onto the surface of the SiO2 particles. Washing removes unreacted APTES and the hydrolysis byproduct ethanol. Drying removes the solvent, yielding SiO2-NH2 with covalently bonded amino groups on the surface. This step introduces a large number of active amino sites onto the surface of the inorganic SiO2 core, providing covalent binding sites for the subsequent nucleation and growth of COF shells on the SiO2 surface, achieving heterogeneous nucleation of COFs on the SiO2 surface.
[0008] S2. Synthesis of sulfonic acid-based covalent organic framework core-shell adsorbent: SiO2-NH2 is added to a methanol solution and ultrasonically treated to ensure uniform mixing; subsequently, 2,4,6-tricarboxymethyl phloroglucinol (Tp), 4,4′-diaminostilbene-2,2′-disulfonic acid (DASD), and 2,5-diaminobenzenesulfonic acid (DBS) monomers are added to the suspension, with the molar ratio of Tp, DASD, and DBS monomers being 2:x:(3-x), where 0 < x < 3. The suspension is then ultrasonically treated again until completely dissolved, and sodium acetate aqueous solution is added as a catalyst. The reaction is stirred at room temperature; the reaction product is centrifuged, washed, and dried to obtain the sulfonic acid-based covalent organic framework core-shell adsorbent.
[0009] Methanol exhibits good solubility for Tp and two sulfonic acid diamine monomers, DASD and DBS, and can also disperse SiO2-NH2 particles. Ultrasonic treatment breaks up particle aggregation, allowing SiO2-NH2 particles to be fully suspended and ensuring sufficient contact between the monomers and the particle surface. Tp contains an aldehyde group (-CHO), while DASD and DBS contain an amino group (-NH2). The two undergo a Schiff base condensation reaction, losing one molecule of water to form an imine bond (-C=N-). The trialdehyde group of Tp undergoes cross-linking polymerization with the diamine monomer to construct a two-dimensional covalent organic framework. Both DASD and DBS possess sulfonic acid groups (-SO3H). After polymerization, the sulfonic acid groups are directly embedded into the COFs framework, achieving intrinsic sulfonic acid functionalization of the COFs shell. The specific process of the Schiff base reaction is as follows: (1) Nucleophilic addition: The amino nitrogen atom acts as a nucleophile, attacking the positively charged carbon atom in the aldehyde group to form an unstable tetrahedral intermediate (i.e., methanol amine compounds); (2) Proton transfer and elimination: This intermediate is unstable and undergoes rapid intramolecular dehydration, eliminating one molecule of water, and finally forming a stable imine structure containing a carbon-nitrogen double bond (-C=N-). The specific process of the Schiff base reaction is shown below:
[0010] Sodium acetate plays a crucial catalyst role in this reaction. Although it does not directly participate in the reaction, it significantly accelerates the reaction process in the following ways: (1) Providing an alkaline environment: Sodium acetate dissociates in water to produce acetate ions, making the reaction system weakly alkaline; (2) Enhancing the nucleophilicity of amino groups: The weakly alkaline environment is conducive to keeping the amino group in a deprotonated free state, making its nitrogen atom have a higher electron cloud density and stronger nucleophilicity, thereby accelerating the nucleophilic attack on the aldehyde carbon; (3) Promoting reversible reaction equilibrium: The formation of Schiff bases is a reversible reaction. The alkaline environment provided by sodium acetate helps to remove the water generated in the reaction in time, pushing the equilibrium towards the formation of imine products and improving the reaction efficiency; (4) Neutralizing acidity and protecting the framework: The sulfonic acid group (-SO3H) in the COFs monomer is acidic, which will inhibit the reactivity of the amino group and may catalyze the hydrolysis of the imine bond; Sodium acetate can effectively neutralize the acidity in the system, protect the newly formed imine bond, and ensure the integrity and stability of the framework structure.
[0011] The synthetic route for the sulfonic acid-based covalent organic framework core-shell adsorbent (COF-Tp-SO3H@SiO2) of this invention can be found in [reference needed]. Figure 1 .
[0012] In a preferred embodiment of the present invention, the reaction temperature in step S1 is 50-60°C and the reaction time is 4-8 h.
[0013] Tp, acting as an aldehyde node, is condensed with sulfonic acid diamines of different chain lengths, DASD and DBS, via Schiff base condensation. The pore size of COFs is directly related to the length of the connecting arms. The longer the connecting arm, the larger the pore size of the constructed framework. The pore size constructed with DASD (long chain) is larger than that constructed with DBS (short chain). Therefore, by systematically changing the molar ratio of these two connecting arms, COF shells with different pore sizes can be formed on the surface of the mesoporous silica core, thereby achieving control over the average pore size of the modified COF shell. By adjusting the molar ratio of DASD to DBS (x:(3-x)), precise control can be achieved over the pore size of the COF shell in the range of 2.0–3.5 nm and the sulfonic acid covalent organic framework core-shell material adsorbent in the range of 6.2–7.6 nm. Preferably, the molar ratio of DASD:DBS is 2:1.
[0014] In a preferred embodiment of the present invention, the concentration of the sodium acetate aqueous solution is 1-5 mol / L, and the amount added is 5%-20% of the total volume of the reaction system.
[0015] In a preferred embodiment of the present invention, in step S2, the mass ratio of Tp to SiO2-NH2 is 4% to 12%, preferably 8%; the reaction time is 2-6 hours, preferably 4 hours.
[0016] The second aspect of the present invention provides a sulfonic acid-based covalent organic framework core-shell material adsorbent, which is prepared according to the preparation method of the sulfonic acid-based covalent organic framework core-shell material adsorbent described in any one of the claims.
[0017] A third aspect of this invention provides the application of a sulfonic acid-based covalent organic framework core-shell material adsorbent as a solid-phase extraction adsorbent in the enrichment and separation of isoquinoline alkaloids. The method of using the sulfonic acid-based covalent organic framework core-shell material adsorbent for the enrichment and separation of sample solutions containing isoquinoline alkaloids includes the following steps: a. The sulfonic acid-based covalent organic framework core-shell material adsorbent is used as an adsorbent packing material and filled into an empty extraction column; the packed solid-phase extraction column is connected to a solid-phase extraction instrument and activated; b. The sample solution containing isoquinoline alkaloids was pretreated before being loaded for adsorption and elution.
[0018] In sulfonic acid covalent organic framework core-shell adsorbents, the sulfonic acid group (-SO3H) ionizes in water to form sulfonate anions (-SO3). - This causes the material surface to carry a negative charge. This is because the sulfonic acid group (-SO3H) is a strong acid functional group, and its acidity originates from the polarization effect of the strong positive charge of the sulfur atom (S) on the OH bond. In aqueous solution, the OH bond of the sulfonic acid group breaks, and hydrogen ions (H+) are released. +It dissociates to form a stable sulfonate anion (-SO3-). - ):
[0019] Because sulfonic acids have extremely low dissociation constants (pKa) (approximately -1 to -2), they are almost completely ionized over a wide pH range (pH>2). Therefore, in most practical applications (such as neutral or weakly acidic aqueous solutions), the sulfonic acid group always dissociates as the negatively charged -SO3 group. - It exists in form.
[0020] Under acidic conditions, the nitrogen atom in an alkaloid molecule undergoes protonation and acquires a positive charge. This is because the protonation process is a reversible dynamic equilibrium, the equilibrium constant of which is determined by the pK of the alkaloid. a Control. According to the Henderson-Hasselbalch equation:
[0021] When the solution pH is lower than the pK of the alkaloid a At this value, the equilibrium shifts strongly to the right (in the protonation direction), and alkaloids mainly exist as protonated cations (BH). + It exists in the form of ) . Because most isoquinoline alkaloids have a pK a With pK values between 7 and 11, under acidic conditions (e.g., pH 2–5), they are fully protonated, thus acquiring a positive charge. The pK values of the nine isoquinoline alkaloids involved in this invention are... a The values range from 7.70 to 11.73 (see Table 9).
[0022] In the core-shell material adsorbent of this invention, sulfonic acid groups are covalently fixed to the framework of the COF shell, and these -SO3 - The functional groups are mainly distributed on the pore surface of COFs and the outer surface of the material, forming a high density of negatively charged sites. Therefore, based on the electrostatic interaction of opposite charges attracting each other, a strong electrostatic attraction is formed between the positively charged protonated alkaloids and the negatively charged composite material surface, thereby achieving efficient enrichment of alkaloid molecules on the surface of the sulfonic acid-based covalent organic framework core-shell material adsorbent.
[0023] Meanwhile, the abundant benzene rings and imine bonds in the aromatic framework of the COFs can form π-π stacking interactions with the aromatic ring system in isoquinoline alkaloid molecules, further enhancing the material's affinity and adsorption stability for alkaloid molecules. Furthermore, the unreacted nitrogen atoms of the imine bonds (-C=N-), the oxygen atoms of the sulfonic acid groups, and the residual silanol groups (Si-OH) on the surface of mesoporous silica in the COFs framework can all form hydrogen bonds with polar groups such as hydroxyl groups (-OH) and amino groups (-NH-) in alkaloid molecules, providing additional recognition and binding sites for the adsorption process. Therefore, the sulfonic acid-based covalent organic framework-modified mesoporous silica core-shell composite material achieves efficient and highly selective separation and enrichment of isoquinoline alkaloids through the synergistic effects of electrostatic interactions provided by sulfonic acid groups, π-π stacking interactions provided by the COFs aromatic framework, hydrogen bonding interactions provided by polar groups, and pore size matching effects. The mechanism of action of the COF-Tp-SO3H@SiO2 material on isoquinoline alkaloids of this invention can be found in [link to relevant documentation]. Figure 2 As shown.
[0024] As a preferred embodiment of the present invention, the isoquinoline alkaloids include tetrandrine, berberine, lotus leaf alkaloid, bordinine, camptothecin, magnoflorine, camphorleaf tetrandrine, black shell nanmu alkaloid, and N-methylene nandina alkaloid.
[0025] In a preferred embodiment of the present invention, the sulfonic acid-based covalent organic framework core-shell material adsorbent is used for the enrichment and separation of camphor seed kernel isoquinoline alkaloid extract.
[0026] In a preferred embodiment of the present invention, the pretreatment of the camphor seed kernel isoquinoline alkaloid extract includes dilution to a concentration of 1-3 mg / mL followed by filtration through a 0.45 μm pore size membrane; the sample loading is performed through the solid phase extraction column at a flow rate of 0.5-1.5 mL / min; after the sample loading is completed, the adsorbent is washed with distilled water to remove impurities; the elution is performed with an 80% ethanol eluent containing 80-120 mM ammonium acetate, the pH of the eluent is 2.0-4.0, and the elution flow rate is 0.5-1.5 mL / min.
[0027] In a preferred embodiment of the present invention, the loading pH of the camphor seed kernel isoquinoline alkaloid extract is 3.0-5.0, and the loading volume is 300-330 mL; the solid phase extraction column has a packing height of 0.7-2.1 cm, and the eluent volume is 325-375 mL.
[0028] As a preferred embodiment of the present invention, the sulfonic acid-based covalent organic framework core-shell material adsorbent can also be used for the enrichment, separation, or content detection of isoquinoline alkaloids in other products, such as bottled water, tea beverages, and milk.
[0029] Compared with the prior art, the present invention has the following beneficial effects: The sulfonic acid-based covalent organic framework core-shell material adsorbent obtained in this invention exhibits excellent adsorption properties for isoquinoline alkaloids in samples, demonstrating advantages such as high adsorption capacity, fast adsorption rate, good adsorption selectivity, and easy recycling. The preparation method of this sulfonic acid-based covalent organic framework core-shell material adsorbent is simple, easy to operate, and conducive to industrial production; it also demonstrates excellent comprehensive adsorption performance for isoquinoline alkaloids in samples, showing promising application prospects.
[0030] (1) Precisely adjustable pore size for selective adsorption: This invention achieves precise and continuous control of the COF shell pore size in the range of 2.0 to 3.5 nm and the sulfonic acid covalent organic framework core-shell material adsorbent in the range of 6.2 to 7.6 nm by adjusting the molar ratio of two sulfonic acid diamine monomers with different chain lengths, DASD and DBS. It can be customized according to the molecular size of the target isoquinoline alkaloid, which significantly improves the adsorption selectivity.
[0031] (2) Synergistic effect of multiple mechanisms, excellent adsorption performance: The material of this invention integrates electrostatic interaction, π-π stacking, hydrogen bonding and pore size matching effect, and exhibits excellent adsorption capacity and selectivity for isoquinoline alkaloids. Experimental results show that after optimized solid-phase extraction, the purity of total alkaloids in the crude extract of camphor tree seed kernels increased from 32.97% to 84.12%, and the recovery rate reached 88.95%.
[0032] (3) Core-shell structure design with good dispersibility and operability: Using mesoporous silica as the core effectively solves the problems of low density, easy agglomeration and difficult column packing of pure COFs materials, reduces the back pressure of solid phase extraction, and improves the convenience and reproducibility of operation.
[0033] (4) Rapid synthesis at room temperature and mild conditions: The present invention uses sodium acetate as a catalyst to rapidly synthesize the COF shell at room temperature, avoiding the high temperature, high pressure and long reaction time required for traditional COF synthesis. It has low energy consumption, simple operation and easy large-scale preparation.
[0034] (5) Strong universality and wide range of applications: The material of this invention is not only applicable to the separation and enrichment of isoquinoline alkaloids in camphor seed kernels, but also applicable to the adsorption and separation of other isoquinoline alkaloids with similar structures. It can also be extended to the sensitive detection of trace isoquinoline alkaloids in complex actual products such as bottled water, tea beverages, and milk. It has good universality and practical application prospects.
[0035] (6) Good stability and reusability: The material of the present invention has excellent chemical and thermal stability. It maintains high adsorption performance after multiple adsorption-desorption cycles and has good reusability.
[0036] (7) The solid-phase extraction separation method provided by the present invention solves the problems of long extraction time and pollution caused by the use of a large amount of organic solvents in the traditional separation and enrichment methods of alkaloid compounds, simplifies the extraction process and embodies the concept of green chemistry. Attached Figure Description
[0037] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0038] Figure 1 This is a schematic diagram of the synthesis route of the COF-Tp-SO3H@SiO2 composite material of the present invention; Figure 2 This is a schematic diagram illustrating the mechanism of action of the COF-Tp-SO3H@SiO2 composite material of the present invention on isoquinoline alkaloids; Figure 3 This is a scanning electron microscope image of the COF-Tp-SO3H@SiO2 composite material of the present invention; Figure 4 This is a transmission electron microscope image of the COF-Tp-SO3H@SiO2 composite material of the present invention; Figure 5 The image shows the FTIR spectrum of the COF-Tp-SO3H@SiO2 composite material of the present invention. Figure 6 The N2 adsorption-desorption curves and pore size distribution diagrams of the COF-Tp-SO3H@SiO2 composite material of the present invention are shown below. Figure 7 The figure shows the effect of adsorption conditions on the adsorption performance of the COF-Tp-SO3H-4@SiO2 composite material. Figure 8 The figure shows the effect of desorption conditions on the desorption performance of COF-Tp-SO3H-4@SiO2 composite material; Figure 9 The dynamic breakthrough curve of solid-phase extraction of the COF-Tp-SO3H@SiO2 composite material of the present invention; Figure 10This diagram illustrates the applicability of the COF-Tp-SO3H@SiO2 composite material of the present invention in the adsorption and separation of various isoquinoline alkaloids. Figure 11 The diagram shows the stability and reusability of the COF-Tp-SO3H@SiO2 composite material of the present invention in the adsorption and separation of alkaloids. Detailed Implementation
[0039] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments. Example 1
[0040] Example 1 of this invention proposes a method for preparing a sulfonic acid-based covalent organic framework core-shell material adsorbent, comprising the following steps: (1) Synthesis of mesoporous SiO2 Mesoporous silica was synthesized using the Stöber method: 10 mL of tetraethyl orthosilicate (TEOS) was added to a mixed solution containing 120 mL of ethanol, 15 mL of water, and 5 mL of ammonia (25–28%). The mixture was stirred at room temperature for 12 h, centrifuged, washed with water and ethanol, and dried at 50 °C to obtain mesoporous SiO2 microspheres (SiO2). BET characterization showed a specific surface area of 333.22 m². 2 / g, pore volume is 0.9864 cm³ 3 / g, with an average pore size of 11.15 nm.
[0041] (2) Aminoation modification of mesoporous SiO2 1.0 g of mesoporous SiO2 was dispersed in 100 mL of ethanol, 3 mL of APTES was added, and the mixture was stirred and refluxed at 55 °C for 6 h. After filtration, the mixture was washed three times with ethanol and dried under vacuum at 55 °C overnight to obtain SiO2-NH2.
[0042] (3) Rapid synthesis of COF shells at room temperature 200 mg of SiO2-NH2 was added to 10 mL of methanol along with Tp, DASD, and DBS monomers weighed according to the molar ratios in Table 1. After ultrasonic dissolution, 2 mL of 3 mol / L sodium acetate aqueous solution was added, and the mixture was stirred at 25 °C for 4 h. After centrifugation, the mixture was washed three times each with deionized water and ethanol, and dried under vacuum at 55 °C for 12 h to obtain COF-Tp-SO3H-1@SiO2, COF-Tp-SO3H-2@SiO2, COF-Tp-SO3H-3@SiO2, COF-Tp-SO3H-4@SiO2, and COF-Tp-SO3H-5@SiO2, respectively.
[0043] Table 1. Composition ratios of COF-Tp-SO3H@SiO2 composite materials with different monomer molar ratios
[0044] Example 2 Example 2 of this invention proposes a method for preparing a sulfonic acid-based covalent organic framework core-shell material adsorbent, comprising the following steps: (1) Synthesis of mesoporous SiO2 Mesoporous silica was synthesized using the Stöber method: 10 mL of tetraethyl orthosilicate (TEOS) was added to a mixed solution containing 120 mL of ethanol, 15 mL of water, and 5 mL of ammonia (25–28%). The mixture was stirred at room temperature for 12 h, centrifuged, washed with water and ethanol, and dried at 50 °C to obtain mesoporous SiO2 microspheres (SiO2). BET characterization showed a specific surface area of 333.22 m². 2 / g, pore volume is 0.9864 cm³ 3 / g, with an average pore size of 11.15 nm.
[0045] (2) Aminoation modification of mesoporous SiO2 1.0 g of mesoporous SiO2 was dispersed in 100 mL of ethanol, 3 mL of APTES was added, the mixture was stirred and refluxed at 50 °C for 8 h, filtered, washed three times with ethanol, and dried under vacuum at 55 °C overnight to obtain SiO2-NH2.
[0046] (3) Rapid synthesis of COF shells at room temperature 200 mg of SiO2-NH2 and Tp, DASD, and DBS monomers weighed according to different mass ratios of Tp to SiO2-NH2 as shown in Table 2 were added to 10 mL of methanol, where the molar ratio of Tp, DASD, and DBS monomers was Tp:DASD:DBS = 2:2:1. After ultrasonic dissolution, 0.5 mL of 5 mol / L sodium acetate aqueous solution was added, and the mixture was stirred at 25 °C for 2 h. After centrifugation, the mixture was washed three times each with deionized water and ethanol, and then vacuum dried at 55 °C for 12 h to obtain COF-Tp-SO3H-4@SiO2 materials with Tp content of 0, 4, 8, 12, 16, and 20% in SiO2-NH2.
[0047] Table 2. Formulation of COF-Tp-SO3H-4@SiO2 composite materials with different Tp contents in SiO2-NH2.
[0048] Example 3 Example 3 of this invention proposes a method for preparing a sulfonic acid-based covalent organic framework core-shell material adsorbent, comprising the following steps: (1) Synthesis of mesoporous SiO2 Mesoporous silica was synthesized using the Stöber method: 10 mL of tetraethyl orthosilicate (TEOS) was added to a mixed solution containing 120 mL of ethanol, 15 mL of water, and 5 mL of ammonia (25–28%). The mixture was stirred at room temperature for 12 h, centrifuged, washed with water and ethanol, and dried at 50 °C to obtain mesoporous SiO2 microspheres (SiO2). BET characterization showed a specific surface area of 333.22 m². 2 / g, pore volume is 0.9864 cm³ 3 / g, with an average pore size of 11.15 nm.
[0049] (2) Aminoation modification of mesoporous SiO2 1.0 g of mesoporous SiO2 was dispersed in 100 mL of ethanol, 3 mL of APTES was added, the mixture was stirred and refluxed at 60 °C for 4 h, filtered, washed three times with ethanol, and dried under vacuum at 55 °C overnight to obtain SiO2-NH2.
[0050] (3) Rapid synthesis of COF shells at room temperature Under the premise of fixing the optimal molar ratio (Tp:DASD:DBS = 2:2:1) and the optimal proportion of Tp to SiO2-NH2 (8%), 200 mg SiO2-NH2, 16 mg Tp, 28.20 mg DASD and 7.17 mg DBS were weighed and added to 10 mL of methanol. After ultrasonic dissolution, 1 mL of 1 mol / L sodium acetate aqueous solution was added, and the reaction was stirred at 25 °C for 0.5-10 h. After centrifugation, the mixture was washed three times each with deionized water and ethanol, and dried under vacuum at 55 °C for 12 h to obtain COF-Tp-SO3H-4@SiO2 materials with different reaction times.
[0051] Structural characterization of COF-Tp-SO3H-1~COF-Tp-SO3H-5@SiO2 composite materials: The surface morphology of the samples was observed using field emission scanning electron microscopy. Before testing, the dried sample powder was uniformly dispersed on a conductive carbon tape, sputtered with gold, and then placed on the electron microscope stage for observation. The microstructure and core-shell morphology of the samples were characterized using transmission electron microscopy. Before testing, a small amount of sample powder was dispersed in anhydrous ethanol, sonicated to ensure thorough dispersion, and then a suitable amount of suspension was dropped onto a copper grid with a carbon support film. After air drying, the sample was placed under an electron microscope for observation. Figure 3 Scanning electron microscope and Figure 4Transmission electron microscopy (TEM) images clearly demonstrate the morphological changes of the material before and after COF modification. Compared with the smooth, regularly spherical original SiO2, the surface roughness of the COF-Tp-SO3H@SiO2 composite material is significantly increased, and the particle edges tend to be blurred. A distinct core-shell structure can be observed in the TEM images, indicating that the COF shell has been successfully coated on the SiO2 surface. EDS analysis further confirmed the elemental composition of the composite material. In addition to Si and O, C, N, and S elements were also detected in the composite material. C and N originated from the organic ligands in the COF backbone, while S came from the sulfonic acid groups in the DASD and DBS monomers. The elements were uniformly distributed on the material surface, further confirming that the COF shell formed a continuous and uniform coating layer on the SiO2 surface.
[0052] The chemical structure and functional groups of the samples were characterized using Fourier transform infrared spectroscopy. The KBr pellet method was employed; the dried sample was mixed with spectrally pure KBr at a ratio of approximately 1:100, ground homogeneously, and then pressed into transparent thin pellets. The measurements were performed in the wavenumber range of 4000–400 cm⁻¹. -1 The scan was performed inside the body at a resolution of 4 cm. -1 The number of scans was 32. Figure 5 Infrared spectra of Tp, DASD, DBS, and COF-Tp-SO3H-1@SiO2~COF-Tp-SO3H-5@SiO2 are shown. In the spectra of the COF-Tp-SO3H-1@SiO2~COF-Tp-SO3H-5@SiO2 composites, the aldehyde group in Tp is at 1635 cm⁻¹. -1 The characteristic stretching vibration peak at 3427 cm⁻¹, and the amino groups in DASD and DBS at 3427 cm⁻¹ -1 and 3334 cm -1 The bimodal peaks of both asymmetric and symmetric stretching vibrations at 1572 cm⁻¹ completely disappeared, indicating that the active functional groups of both monomers had fully participated in the condensation reaction. Meanwhile, the COFs sample at 1572 cm⁻¹... -1 A new strong absorption peak appeared at approximately 1220 cm⁻¹, attributed to the stretching vibration of the imine bond (C=N), confirming the successful construction of a covalently linked framework structure between Tp and DASD / DBS via Schiff base polymerization. Furthermore, a new strong absorption peak appeared at approximately 1220 cm⁻¹. -1 The characteristic peak of S=O at approximately 820 cm⁻¹ -1 The SO stretching vibration peak at 1450 cm⁻¹ further confirmed the presence of sulfonic acid groups, indicating that DASD and DBS monomers had been successfully introduced into the COFs framework. The COFs spectrum also retained the 1450 cm⁻¹ peak. -1 The stretching vibration peak of the benzene ring and 780 cm⁻¹ -1The out-of-plane bending vibration peaks of the aromatic rings are consistent with the aromatic structures of Tp, DASD, and DBS, indicating that the aromatic conjugated skeleton of COFs remains intact after the reaction, providing a structural basis for the π-π stacking interaction during the adsorption process.
[0053] The specific surface area, pore volume, and pore size distribution of the samples were characterized using a fully automated specific surface area and pore size analyzer. Before testing, the samples were vacuum degassed at 100 °C for 6 h to remove adsorbed moisture and impurities from the sample surface and pores. Using high-purity nitrogen as the adsorbate, nitrogen adsorption-desorption experiments were conducted at liquid nitrogen temperature of 77 K to obtain the specific surface area and pore size distribution. Figure 6 The BET characterization results in Table 3 are as follows: Among all composite materials, COF-Tp-SO3H-4@SiO2 (Tp:DASD:DBS=2:2:1) has the highest BET specific surface area (299.94 m²). 2 / g), while maintaining a suitable pore volume (0.47 cm³). 3 The specific surface area (S / g) and pore size (6.27 nm) are also significant. This pore size is approximately 4–6 times the molecular size of the target isoquinoline alkaloid (1.05–1.54 nm), which facilitates the diffusion and adsorption of the target molecule within the pores. When the DASD ratio is further increased to Tp:DASD:DBS=2:3:0 (COF-Tp-SO3H-5@SiO2), the specific surface area decreases sharply to 261.16 m². 2 / g, pore volume decreased to 0.4067 cm³. 3 The / g ratio indicates that excessive long-chain monomers may lead to loose COF layer stacking and reduced structural order due to steric hindrance, thus reducing the effective specific surface area. Therefore, an appropriate DASD to DBS ratio is crucial for optimizing the pore structure parameters of composite materials.
[0054] Table 3. BET specific surface area and pore size distribution of SiO2 and COF-Tp-SO3H@SiO2
[0055] Example 4 Example 4 provides a COF-Tp-SO3H@SiO2 core-shell material for the enrichment and separation of alkaloids from camphor tree seeds.
[0056] (1) Effect of COF-Tp-SO3H@SiO2 core-shell composite material on the adsorption capacity of total alkaloids in camphor seed kernels High-performance liquid chromatography (HPLC) method for the determination of alkaloid content: Chromatographic conditions: Alkaloid samples were quantitatively analyzed using an Agilent 1260 Infinity III high-performance liquid chromatography system equipped with a variable wavelength detector (VWD). Sample solutions were filtered through a 0.22 μm organic filter before injection. Chromatographic separation was performed using an Amethyst C18-H reversed-phase column (4.6 mm × 250 mm, 5.0 μm) at 25 ℃, a flow rate of 1.0 mL / min, and an injection volume of 5 μL. The mobile phase consisted of 0.1% (v / v) formic acid aqueous solution (phase A) and methanol (phase B), using a gradient elution method. The elution program was as follows: 0–8 min, 5–20% B; 8–28 min, 20–50% B; 28–40 min, 50–85% B; 40–45 min, 85–5% B; 45–55 min, 5% B. The VWD detection wavelength was 280 nm.
[0057] Establishment of standard curves: The external standard method was used to quantitatively analyze the content of alkaloids in the samples. Accurately weigh 4 mg each of nine isoquinoline alkaloid standards (magnoliaine, fangchiine, black peonyine, N-methylene nancholine, tetrandrine, berberine, lotus leaf alkaloid, bortine, and camptothecin) and place them in separate 10 mL volumetric flasks. Dissolve in methanol and dilute to the mark to prepare a standard stock solution with a concentration of 0.4 mg / mL. Accurately pipette 0.025, 0.05, 0.25, 0.5, 1.0, 1.5, and 2.0 mL of the above stock solution into separate 2 mL volumetric flasks, dilute to the mark with methanol, and mix well to obtain a series of mixed standard working solutions with concentrations of 5, 10, 50, 100, 200, 300, and 400 μg / mL. A standard curve was plotted with the peak area (mAU·s) of each alkaloid standard as the ordinate (y) and the corresponding mass concentration (μg / mL) as the abscissa (x). Linear regression was then performed to obtain the regression equations and correlation coefficients (R²) for the nine representative isoquinoline alkaloids. 2 As shown in Table 4.
[0058] Table 4. Standard curves for 9 representative isoquinoline alkaloids
[0059] Calculate the adsorption rate, adsorption capacity, desorption rate, desorption amount, recovery rate, and purity using the following formulas:
[0060]
[0061]
[0062]
[0063]
[0064]
[0065] Where A: adsorption rate; C0: concentration of solution before adsorption, mg / mL; C e Q: Concentration of the solution after adsorption, mg / mL; e Adsorption capacity, mg / g; V i D: Solution volume, mL; C: Desorption rate; d : Concentration of the solution after desorption, mg / mL; V d Q: Desorption volume, mL; d W: Desorption capacity, mg / g; R: Adsorbent dosage, g; C: Recovery rate; 测 : Sample solution concentration (mg / mL) calculated from the standard curve; V 总 : Final volume of sample (mL); m 样品 : The mass (mg) of the sample to be tested.
[0066] 100 mg of COF-Tp-SO3H-1@SiO2 to COF-Tp-SO3H-5@SiO2 core-shell materials were weighed and placed in 15 mL of 2 mg / mL alkaloid sample solution. Adsorption was carried out at room temperature with shaking for 6 h, followed by centrifugation. The supernatant was then used for HPLC analysis. Table 5 shows that the COF-Tp-SO3H-4@SiO2 core-shell composite material exhibited optimal adsorption performance when the molar ratio of Tp, DASD, and DBS was 2:2:1, with an adsorption rate of 49.08% and an adsorption capacity of 58.57 mg / g. At this ratio, the DASD to DBS molar ratio of 2:1 ensured sufficient sulfonic acid group density and formed a suitable pore size, which was beneficial for the diffusion and adsorption of alkaloid molecules. Therefore, the optimal molar ratio of Tp, DASD, and DBS was 2:2:1.
[0067] Table 5. Effects of different molar ratios of COF-Tp-SO3H-1@SiO2 and COF-Tp-SO3H-5@SiO2 on the adsorption capacity of camphor seed kernel alkaloids.
[0068] Example 2 investigated the effect of the proportion of Tp in SiO2-NH2 on the adsorption of total alkaloids under the premise of a fixed optimal molar ratio (Tp:DASD:DBS = 2:2:1). Table 6 shows that the adsorption effect is optimal when the proportion of Tp in SiO2-NH2 is 8%. If the proportion is too low, there are insufficient effective adsorption sites; if the proportion is too high, the excessively thick COF layer may lead to pore blockage or decreased dispersibility, which is detrimental to adsorption. Therefore, the optimal proportion is 8%.
[0069] Table 6. Effect of different Tp-to-SiO2 ratios on the adsorption capacity of camphor seed kernel alkaloids on COF-Tp-SO3H@SiO2 prepared by COF-Tp-SO3H@SiO2 on camphor seed kernel alkaloids
[0070] Example 3 investigated the effect of different reaction times on adsorption performance under the premise of a fixed optimal molar ratio (Tp:DASD:DBS = 2:2:1) and the optimal Tp percentage of SiO2-NH2 (8%). Table 7 shows that the adsorption performance gradually increases with increasing reaction time, but the adsorption amount no longer increases significantly after 4 hours. The optimal reaction time is 4 hours. If the time is too short, COFs crystallization is incomplete, and the active sites are insufficiently exposed; if the time is too long, the imine bonds may partially hydrolyze or the pore structure may collapse, leading to a decrease in adsorption capacity. Therefore, the optimal reaction time is 4 hours.
[0071] Table 7. Effect of COF-Tp-SO3H@SiO2 core-shell composite materials prepared at different reaction times on the adsorption capacity of camphor seed kernel alkaloids.
[0072] (2) Effect of COF-Tp-SO3H-4@SiO2 core-shell composite material on the adsorption capacity of total alkaloids in camphor seed kernels under different adsorption conditions The effects of solution pH, adsorption temperature, and adsorption time on the adsorption effect are as follows: Figure 7 As shown.
[0073] Effect of solution pH: 100 mg of COF-Tp-SO3H-4@SiO2 was added to sample solutions with pH values of 2.0-12.0, and the solutions were placed in a constant temperature shaker at 25 ℃ and 150 r / min for 12 h for adsorption. The contents of total alkaloids in camphor seed kernels were then determined. Figure 7(A) shows that as the pH increases from 2.0 to 4.0, both the adsorption rate and the adsorption capacity gradually increase, reaching their maximum values at pH 4.0, at 89.56% and 125.01 mg / g, respectively. Thereafter, as the pH continues to rise to 12.0, the adsorption performance gradually decreases. This trend can be attributed to the electrostatic interaction between the adsorbent and the alkaloid molecules. The sulfonic acid groups on the adsorbent surface remain negatively charged over a wide pH range, while the pKa values of the four alkaloids from camphor seed kernels range from approximately 8.676 to 9.111 (see Table 9). When the solution pH is lower than their pKa, the alkaloids protonate and become positively charged. At pH 4.0, the alkaloids are fully protonated, generating the strongest electrostatic attraction with the negatively charged adsorbent, thus achieving the highest adsorption efficiency. As the pH increases, the alkaloids gradually deprotonate, the positive charge decreases, the electrostatic interaction weakens, and the adsorption performance declines accordingly. Therefore, pH 4.0 was chosen as the optimal adsorption condition for subsequent experiments.
[0074] Effect of adsorption temperature: 100 mg of COF-Tp-SO3H-4@SiO2 was added to a sample solution with pH 4.0 and placed in a constant temperature shaker at 25, 35, 45, 55 and 65 ℃ and 150 r / min for 12 h for adsorption. The contents of total alkaloids in camphor seed kernels were then determined. Figure 7 (B) indicates that both the adsorption rate and the adsorption amount gradually decrease as the temperature increases from 25℃ to 65℃, suggesting that the adsorption process is exothermic. Low temperatures favor adsorption equilibrium, while high temperatures shift the equilibrium towards desorption. Therefore, 25℃ was chosen as the optimal adsorption temperature.
[0075] Effect of adsorption time: 100 mg of COF-Tp-SO3H-4@SiO2 was added to the sample solution at pH 4.0 and placed in a constant temperature shaker at 25℃ and 150 r / min for adsorption. The total alkaloid content of camphor seed kernels was determined after 0.25, 0.5, 1.0, 2.0 and 3.0 h. Figure 7 (C) indicates that the adsorption rate stabilized after 1 h, indicating that adsorption had reached equilibrium. In summary, the optimal adsorption conditions were determined to be: 100 mg of COF-Tp-SO3H-4@SiO2, a solution concentration of 2.0 mg / mL, a volume of 15 mL, pH 4.0, an adsorption temperature of 25 ℃, and an adsorption time of 1 h. Under these conditions, the adsorption capacity of the COF-Tp-SO3H-4@SiO2 core-shell composite material for the total alkaloids of camphor tree seeds was 122.15 mg / g.
[0076] (3) Effect of COF-Tp-SO3H-4@SiO2 core-shell composite material on the adsorption capacity of total alkaloids in camphor seed kernels under different desorption conditions The effects of ammonium acetate concentration, pH of the desorption solution, desorption temperature, and desorption time on the adsorption effect are as follows: Figure 8 As shown.
[0077] Effect of ammonium acetate concentration in the desorption solution: COF-Tp-SO3H-4@SiO2 in adsorption equilibrium was added to 15 mL of 80% ethanol solution of 0-125 mM ammonium acetate, and placed in a constant temperature shaker at 25℃ and 150 r / min for 12 h for desorption. The total alkaloid content of camphor seed kernels was then determined. Figure 8 (A) indicates that the desorption capacity is lowest when only 80% ethanol is used as the desorbent, suggesting that organic solvents alone are insufficient to effectively disrupt the strong interaction between COF-Tp-SO3H-4@SiO2 and the alkaloids. To further improve the desorption efficiency, ammonium acetate was introduced as a modifier into 80% ethanol. The NH4+ produced by the ionization of ammonium acetate... + Ions can compete with positively charged alkaloids for -SO3- sites on the adsorbent surface, displacing the target alkaloids through an ion exchange mechanism. The desorption rate gradually increases as the ammonium acetate concentration increases from 0 to 100 mM; further increases in ammonium acetate concentration do not increase the desorption rate further. When the ammonium acetate concentration is 100 mM, the desorption rate of each alkaloid exceeds 80%. Therefore, an 80% ethanol solution containing 100 mM ammonium acetate is selected as the desorbent.
[0078] Effect of pH on desorption solution: COF-Tp-SO3H-4@SiO2 at adsorption equilibrium was added to 15 mL of 80% ethanol solution containing 100 mM ammonium acetate with pH 2.0-12.0, and placed in a constant temperature shaker at 25℃ and 150 r / min for 12 h for desorption. The total alkaloid content of camphor tree seed kernels was then determined. Figure 8 (B) indicates that the desorption rate reaches its maximum at pH 3.0 and decreases to its minimum at pH 7.0. Under acidic conditions (pH 2–4), high concentrations of H+... + The dissociation of sulfonic acid groups was inhibited, weakening the electrostatic attraction and thus promoting desorption. Under alkaline conditions (pH 9–12), the alkaloids gradually deprotonated and transformed into neutral molecules, the electrostatic effect disappeared, and the desorption rate increased again. These results indicate that electrostatic attraction is the dominant adsorption mechanism, and the desorption process can be effectively controlled by adjusting the pH of the desorption solution. It is noteworthy that the alkaloids obtained at pH 3.0 have higher purity, while pH 9.0–12.0 leads to co-elution of proteins or acidic impurities, resulting in decreased purity. Therefore, considering both desorption rate and product purity, pH 3.0 was determined to be the optimal pH for the desorption solution.
[0079] Effect of desorption temperature: COF-Tp-SO3H-4@SiO2 in adsorption equilibrium was added to 15 mL of 80% ethanol solution containing 100 mM ammonium acetate at pH 3.0. The solutions were placed in constant temperature shakers at 25, 30, 35, 40 and 45 °C and 150 r / min for 12 h for desorption. The total alkaloid content of camphor tree seed kernels was then determined. Figure 8 (C) indicates that the desorption capacity increases slightly as the temperature rises from 25 °C to 45 °C. Therefore, considering practical factors such as energy saving and maintaining the stability of the alkaloids, 25 °C is selected as the optimal desorption temperature.
[0080] Effect of desorption time: COF-Tp-SO3H-4@SiO2 at adsorption equilibrium was added to 15 mL of 80% ethanol solution containing 100 mM ammonium acetate at pH 3.0 and placed in a constant temperature shaker at 25 ℃ and 150 r / min for desorption. The total alkaloid content of camphor tree seed kernels was determined after 0.25, 0.5, 1.0, 2.0 and 3.0 h. Figure 8 (D) indicates that the desorption rate increases significantly with increasing desorption time from 0.25 h to 0.5 h, and stabilizes after 0.5 h, indicating that desorption has reached equilibrium. In summary, the optimal conditions for static desorption are: an 80% ethanol solution containing 100 mM ammonium acetate, a pH of 3.0, a desorption temperature of 25 ℃, and a desorption time of 0.5 h. Under these conditions, the desorption capacity of the COF-Tp-SO3H-4@SiO2 core-shell composite material for the total alkaloids in camphor tree seeds is 117.11 mg / g.
[0081] (4) Effect of solid-phase extraction conditions of COF-Tp-SO3H-4@SiO2 core-shell material on the adsorption capacity of camphor seed kernel alkaloids Preparation of solid-phase extraction (SPE) columns: The COF-Tp-SO3H-4@SiO2 core-shell material prepared above was used as the adsorbent packing material and filled into empty extraction columns with filling heights of 0.7, 1.4, and 2.1 cm. Sample preparation: Samples containing camphor seed kernel isoquinoline alkaloids were dissolved in ultrapure water to form homogeneous solutions with concentrations of 1, 2, and 3 mg / mL. All diluted sample solutions were filtered through a 0.45 μm pore size membrane and stored at 4 ℃ for further SPE processing. Solid-phase extraction: Activation: The SPE columns were activated and cleaned with ethanol and distilled water, respectively. Sample loading: Sample solutions were passed through the SPE columns at certain flow rates (0.5, 1.0, and 1.5 mL / min) to ensure sufficient contact with the COF-Tp-SO3H-4@SiO2 core-shell material adsorbent for adsorption. The sample loading volume was 320 mL. The camphor seed kernel alkaloids adsorbed by the adsorbent were eluted with an eluent (80% ethanol solution containing 100 mM ammonium acetate, pH 3.0). The volume of the eluent was 350 mL to achieve enrichment and separation. An automated sample collector was used to collect the eluent and desorbate for HPLC analysis.
[0082] Figure 9 Based on the comprehensive analysis of Table 8, the optimal enrichment and separation conditions are: a packing height of 1.4 cm, a sample concentration of 2.0 mg / mL, and a loading flow rate of 1.0 mL / min. HPLC analysis showed that under the above optimal separation conditions, the purity of total alkaloids in the eluent increased from 32.97% of the crude extract to 84.12%, and the recovery rate was 88.95%.
[0083] Table 8. Adsorption effect of camphor seed kernel alkaloids under solid-phase extraction conditions using COF-Tp-SO3H-4@SiO2 core-shell material.
[0084] (5) Applicability, acid and alkali resistance and reusability of COF-Tp-SO3H-4@SiO2 core-shell material To investigate the adsorption applicability of the COF-Tp-SO3H-4@SiO2 core-shell composite material of this invention to isoquinoline alkaloids with different structures, static adsorption experiments were conducted on nine representative isoquinoline alkaloids, namely tetrandrine (TET), berberine (BBR), nuciferine (NF), bortine (BD), camptothecin (CPT), magnoflorine (MAG), lauryl tetrandrine (LAU), linalool (LIN), and N-methylene nancholine (N-Dom). The structures and physicochemical properties are shown in Table 9. Figure 10The results indicate that the adsorbent exhibits high adsorption capacity for all nine alkaloids mentioned above, with the highest adsorption capacity for LIN and N-Dom, followed by MAG, LAU, BD, and CPT, and relatively low adsorption capacity for TET, BBR, and NF. This difference in selective adsorption is attributed to the structural differences among the different alkaloids in terms of conjugation systems, substituent patterns, and molecular geometry. These structural features influence the strength of hydrogen bonds, electrostatic interactions, and π-π stacking interactions between the alkaloids and the adsorbent. These results demonstrate that the adsorbent of this invention has broad-spectrum adsorption applicability for a variety of isoquinoline alkaloids.
[0085] Table 9. Structure and physicochemical properties of nine representative isoquinoline alkaloids
[0086]
[0087]
[0088] pK a The acid dissociation constant, HA (number of hydrogen bond acceptors), and HD (number of hydrogen bond donors) can all be obtained from the PubChem database of the National Center for Biotechnology Information (NCBI) (https: / / pubchem.ncbi.nlm.nih.gov / ).
[0089] To evaluate the chemical stability of the COF-Tp-SO3H-4@SiO2 core-shell composite material of the present invention, the adsorbent was immersed in solutions with pH 2.0 to 12.0 for 12 hours, and its adsorption performance for the target alkaloid was measured. Figure 11 (A) indicates that the adsorption efficiency of this adsorbent remains essentially constant within the pH range of 3.0–11.0, with only a slight decrease under strong acid (pH 2.0) or strong base (pH 12.0) conditions. This is because the rigid framework of COF-Tp-SO3H-4@SiO2 effectively prevents the hydrolysis of imine bonds, allowing the composite material to maintain structural integrity over a wide pH range. These results demonstrate that the adsorbent of this invention exhibits excellent acid and base tolerance and can adapt to real-world sample pretreatment environments with significant pH fluctuations.
[0090] To further investigate the reusability of the COF-Tp-SO3H-4@SiO2 core-shell composite material of the present invention, after each desorption was completed, the adsorbent was washed with ethanol and distilled water in sequence until neutral, and then used for the next adsorption experiment. Figure 11 Figure (B) shows that after 10 adsorption-desorption cycles, the adsorption rate of the adsorbent remains above 80%. These results indicate that the adsorbent of this invention has good reusability, can be recycled multiple times, and maintains a high adsorption efficiency.
[0091] Example 5: Application of COF-Tp-SO3H-4@SiO2 core-shell material for enriching and detecting alkaloids in real samples Spiked recovery experiments were conducted on bottled water, tea, and milk samples. Six alkaloids were added (magnoliaine, fangchiine, tetrandrine, N-methylene fangchiine, and berberine at concentrations of 5, 10, and 25 μg / mL; and berberine at concentrations of 10, 20, and 50 μg / mL; the pH of all samples was adjusted to 4.0). After solid-phase extraction with COF-Tp-SO3H-4@SiO2, the target analytes were quantitatively analyzed by HPLC. Intra-day precision and inter-day precision were evaluated by three parallel determinations within the same day and repeated determinations over three consecutive days (n=3), respectively. The results in Table 10 show that the recoveries of the six alkaloids in the three matrices ranged from 93.55% to 102.47%, with intra-day RSD < 3.34% and inter-day RSD < 1.96%, indicating that the method of the present invention has good accuracy and precision and is suitable for the sensitive detection of trace isoquinoline alkaloids in complex samples.
[0092] Table 10 Analytical results of six isoquinoline alkaloids in actual samples
[0093] Nd: Not detected.
[0094] Comparative Example 1 Equal amounts of 100 mg adsorbent were used to compare the adsorption effects of different adsorbents on total alkaloids from camphor tree seeds under the following conditions: concentration of isoquinoline alkaloids in camphor seed kernel solution of 2.0 mg / mL, volume of 15 mL, pH 4.0, adsorption temperature of 25 ℃, and adsorption time of 1 h. Table 11 shows that COF-Tp-SO3H-4@SiO2 showed significantly higher adsorption effects on total alkaloids from camphor seed kernels than other commercial adsorbents, including C18, macroporous resins (AB-8, XR918C, and HJ-18), and cation exchange resins.
[0095] Table 11 Comparison of the adsorption effects of different adsorbents on total alkaloids in camphor tree seed kernels
[0096] Comparative Example 2 The preparation method of the sulfonic acid-based covalent organic framework core-shell material adsorbent in Comparative Example 2 differs from that in Example 1 only in that the step of adding 2 mL of 3 mol / L sodium acetate aqueous solution is omitted in step (3). All other treatments are the same as in Example 1. Table 12 shows that the adsorbent prepared without the addition of sodium acetate catalyst exhibits a significant decrease in adsorption performance for total alkaloids from camphor tree seeds. This is because, in the absence of a catalyst, the Schiff base condensation reaction rate between aldehydes and amino groups is extremely slow, resulting in a large number of monomers failing to effectively participate in the polymerization reaction and making it difficult to form a regular COF pore structure. Simultaneously, due to the low orderliness of the framework, most pores collapse due to structural disorder or are blocked by unreacted monomers, further reducing the effective specific surface area and the accessibility of active sites. Therefore, the adsorption capacity and adsorption rate of the adsorbent prepared in Comparative Example 2 for total alkaloids from camphor tree seeds are far lower than those in Example 1.
[0097] Table 12 Comparison of the adsorption effects of different adsorbents on total alkaloids in camphor tree seed kernels
[0098] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A method for preparing a sulfonic acid-based covalent organic framework core-shell material adsorbent, characterized in that, Includes the following steps: Preparation of S1 and SiO2-NH2: Mesoporous SiO2 was dispersed in ethanol, APTES was added, the mixture was stirred and refluxed, and SiO2-NH2 was obtained after washing and drying. S2. Synthesis of sulfonic acid-based covalent organic framework core-shell material adsorbent: SiO2-NH2 is added to a methanol solution and ultrasonically treated to ensure uniform mixing; Tp, DASD, and DBS monomers are added to the suspension, wherein the molar ratio of Tp, DASD, and DBS monomers is 2:x:(3-x), where 0 < x < 3. The suspension is further ultrasonically treated until completely dissolved, and then sodium acetate aqueous solution is added as a catalyst. The reaction is stirred at room temperature; the reaction product is centrifuged, washed, and dried to obtain the sulfonic acid-based covalent organic framework core-shell material adsorbent.
2. The method for preparing the sulfonic acid-based covalent organic framework core-shell material adsorbent according to claim 1, characterized in that, In step S1, the reaction temperature is 50–60°C and the reaction time is 4–8 h.
3. The method for preparing the sulfonic acid-based covalent organic framework core-shell material adsorbent according to claim 2, characterized in that, The concentration of the sodium acetate aqueous solution is 1-5 mol / L, and the amount added is 5%-20% of the total volume of the reaction system.
4. The method for preparing the sulfonic acid-based covalent organic framework core-shell material adsorbent according to claim 3, characterized in that, In step S2, the mass ratio of Tp to SiO2-NH2 is 4% to 12%; the reaction time is 2 to 6 hours.
5. A sulfonic acid-based covalent organic framework core-shell adsorbent, characterized in that, It is prepared by the method for preparing sulfonic acid-based covalent organic framework core-shell material adsorbents according to any one of claims 1-4.
6. The application of sulfonic acid-based covalent organic framework core-shell material adsorbents as solid-phase extraction adsorbents in the enrichment and separation of isoquinoline alkaloids, characterized in that... The use of the sulfonic acid-based covalent organic framework core-shell material adsorbent according to claim 5 for the enrichment and separation of sample solutions containing isoquinoline alkaloids includes the following steps: a. The sulfonic acid-based covalent organic framework core-shell material adsorbent described in claim 5 is used as an adsorbent packing material to fill an empty extraction column; the packed solid-phase extraction column is connected to a solid-phase extraction instrument and activated; b. The sample solution containing isoquinoline alkaloids was pretreated before being loaded for adsorption and elution.
7. The application according to claim 6, characterized in that, The isoquinoline alkaloids include tetrandrine, berberine, lotus leaf alkaloid, bordinine, camptothecin, magnoflorine, camphorleaf tetrandrine, black shell nanmu alkaloid, and N-methylene nandina alkaloid.
8. The application according to claim 6, characterized in that, The sulfonic acid-based covalent organic framework core-shell material adsorbent described in claim 5 was used for the enrichment and separation of isoquinoline alkaloid extract from camphor tree seeds.
9. The application according to claim 8, characterized in that, The pretreatment of the camphor seed kernel isoquinoline alkaloid extract includes dilution to a concentration of 1-3 mg / mL followed by filtration through a 0.45 μm pore size membrane; the loading is performed through the solid phase extraction column at a flow rate of 0.5-1.5 mL / min; after loading, the adsorbent is washed with distilled water to remove impurities; the elution is performed with 80% ethanol eluent containing 80-120 mM ammonium acetate, the pH of the eluent is 2.0-4.0, and the elution flow rate is 0.5-1.5 mL / min.